Penyuluhan Literasi Budidaya Komoditi Kelor dalam Mencegah Stunting dan Pengolahan Bernilai Ekonomis di Desa Medan Sinembah, Kecamatan Tanjung Morawa, Kabupaten Deli Serdang - Isnan Nisa Nasution; Darmina Eka Sari Rangkuti (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to increase community literacy regarding the cultivation and utilization of moringa (Moringa oleifera) as a stunting prevention strategy while simultaneously opening economic opportunities through processing value-added products. The program was implemented in Medan Sinembah Village, Tanjung Morawa District, Deli Serdang Regency, using a participatory approach through outreach, cultivation training, food processing demonstrations, and mentoring of family micro-enterprises. The implementation method used a practice-based community education model with pre-post evaluations to measure participants' understanding. Results showed increased community knowledge about the nutritional value of moringa, product processing skills, and the emergence of business opportunities based on processed moringa products. This activity demonstrates that utilizing local resources through an economic and nutritional literacy approach can have both social and economic impacts. This program is recommended for sustainable development through synergy between villages, universities, and local business groups.